Geochemometric Assessment of Primordial Radionuclides and Trace Elements in Coastal Sediments: Environmental and Radiological Implications for South India - B. Goswami (International Journal of Minerals, 2024)
This study focuses on environmental radioactivity and trace element contamination in coastal sediments along the southern region of the Indian subcontinent, from the Palar River to Pulicat Lake. Utilizing gamma-ray spectroscopy with a NaI (Tl) detector, along with atomic absorption spectroscopy, the research examines the spatial distribution and activity concentrations of primordial radionuclides—namely, 238U, 232Th, and 40K—as well as trace elements such as Ni, Pb, Mn, Zn, Cu, Co, Fe, and Cr. Gamma radiation levels were measured using a MiniTRACE CSDF survey meter, providing key data on the gamma dosage levels in the studied sediments. The concentrations of primordial radionuclides in the sediment samples ranged from ≤3 to 1953 Bq/kg for 238U, ≤3 to 1180 Bq/kg for 232Th, and 41 to 753 Bq/kg for 40K. Among these, 40K showed the highest contribution to the dose rate, highlighting its significant radiological impact. Additionally, the study conducted geochemometric analyses to evaluate the radiological risks and calculate hazard indices associated with both naturally occurring radioactive materials (NORM) and toxic elements present in the environment. This comprehensive investigation provides valuable insights into the environmental impact of radionuclides and trace elements in coastal ecosystems. The findings carry important implications for radiation safety, environmental monitoring, and public health protection, particularly for coastal populations who may be exposed to elevated levels of radioactivity and trace metal contamination through various environmental pathways. Consequently, the study underscores the need for ongoing monitoring and regulation to mitigate potential health risks.
Keywords: Environmental radioactivity; coastal sediments; geochemometrics; primordial radionuclides; trace elements